Mathematics
courtneydale1999
2

Solve by any method of your choosing. 1. y = x - 1                                     2. 3x - y = 8      2x + y = 5                                      y - 3x = -2

+0
(1) Answers
rishimisra15

Let us solve the first problem by substitution y = x-1 2x + y = 5 substituting the value of y in equation 2, 2x + (x-1) = 5 = 2x + x = 5+ 1 = 6 3x = 6 thus, x = 6/3 = 2 Now, y = x -1 = 2 - 1 =1. Thus, x = 2 , y = 1 Now for the second one :  3x - y = 8 y-3x = -2  Thus, by eq. 2, y = 3x - 2 Substituting the value of y in equation 1, 3x - (3x-2) = 8 = 3x - 3x = 10 thus, 0 = 10 ; which is a false statement Thus, it has no solutions

Add answer